Salivary Lactoferrin Expression in a Mouse Model of Alzheimer’s Disease - Antequera, Desiree; Moneo, Diego; Carrero, Laura; Bartolome, Fernando; Ferrer, Isidro; Proctor, Gordon; Carro, Eva (Frontiers in Immunology, 2021)
In the last few years, microbial infection and innate immune theories have been proposed as an alternative approach explaining the etiopathogenesis and origin of Alzheimer’s disease (AD). Lactoferrin, one of the main antimicrobial proteins in saliva, is an important modulator of immune response and inflammation, and represents an important defensive element by inducing a broad spectrum of antimicrobial effects against microbial infections. We demonstrated that lactoferrin levels in saliva are decreased in prodromal and dementia stages of AD compared with healthy subjects. That finding seems to be specific to cerebral amyloid-β (Aβ) load as such observation was not observed in healthy elderly controls or those subjects with frontotemporal dementia. In the present study, we analysed salivary lactoferrin levels in a mouse model of AD. We observed robust and early reduction of lactoferrin levels in saliva from 6- and 12-month-old APP/PS1 mice. Because saliva is secreted by salivary glands, we presume that deregulation in salivary glands resulting in reduced salivary lactoferrin levels may occur in AD. To test this hypothesis, we collected submandibular glands from APP/PS1 mice, as well as submandibular gland tissue from AD patients and we analysed the expression levels of key components of the salivary protein signalling pathway. A significant reduction in M3 receptor levels was found along with decreased acetylcholine (Ach) levels in submandibular glands from APP/PS1 mice. Similarly, a reduction in M3 receptor levels was observed in human submandibular glands from AD patients but in that case, the Ach levels were found increased. Our data suggest that the ACh-mediated M3 signalling pathway is impaired in salivary glands in AD, resulting in salivary gland dysfunction and reduced salivary lactoferrin secretion.